Caffeine exposure in utero is associated with structural brain alterations and deleterious neurocognitive outcomes in 9–10 year old children. (15th March 2021) - Christensen, Zachary P.; Freedman, Edward G.; Foxe, John J.
Abstract: Caffeine, a very widely used and potent neuromodulator, easily crosses the placental barrier, but relatively little is known about the long-term impact of gestational caffeine exposure (GCE) on neurodevelopment. Here, we leverage magnetic resonance imaging (MRI) data, collected from a very large sample of 9157 children, aged 9–10 years, as part of the Adolescent Brain and Cognitive Development sm (ABCD ®) study, to investigate brain structural outcomes at 27 major fiber tracts as a function of GCE. Significant relationships between GCE and fractional anisotropy (FA) measures in the inferior fronto-occipito fasciculus and corticospinal tract of the left hemisphere (IFOF-LH; CST-LH) were detected via mixed effects binomial regression. We further investigated the interaction between these fiber tracts, GCE, cognitive measures (working memory, task efficiency), and psychopathology measures (externalization, internalization, somatization, and neurodevelopment). GCE was associated with poorer outcomes on all measures of psychopathology but had negligible effect on cognitive measures. Higher FA values in both fiber tracts were associated with decreased neurodevelopmental problems and improved performance on both cognitive tasks. We also identified a decreased association between FA in the CST-LH and task efficiency in the GCE group. These findings suggest that GCE can lead to future neurodevelopmental complications and that this occurs, in part, through alteration of the microstructure of critical fiber tracts such as the IFOF-LH and CST-LH. These data suggest that current guidelines regarding limiting caffeine intake during pregnancy may require some recalibration. Highlights: Caffeine is a known neuromodulator that is commonly consumed throughout pregnancy. 4, 135 mothers reported consuming caffeine more than once a week throughout gestation in a sample of 9, 157. Decreased fractional anisotropy in the left IFOF and CST fiber tracts were associated with gestational caffeine exposure. Measures related to psychopathology were elevated in those with gestational caffeine exposure. Gestational caffeine exposure modulated the relationship between task efficiency and fractional anisotropy in the left CST.